1971
DOI: 10.1111/j.1550-7408.1971.tb03384.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of the Cyst Wall of the Ciliated Protozoon Didinium nasutum1

Abstract: SYNOPSIS. Electron microscope observations of the complex cyst wall of Didinium nasutum are reported. The cyst wall is composed of 3 major coats. The outermost coat, the ectocyst, consists of short strands of filamentous material which forms a diffuse, amorphous layer approximately 8–9 μ thick. Culture debris, bacteria and unidentified inclusions have been observed adhering to the outer coat. The mesocyst, approximately 2.5 μ thick, has 2 distinct regions. The outer region is differentiated into several sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1973
1973
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…This is also the case in encysting Gastrostyla steinii. The lamellar structure is similar to that noted for the inner mesocyst of the gymnostome Didinium nasutum (Holt & Chapman, 1971). It appears that the "herringbone" structure of the mesocyst is a transition state for the predominantly lamellar mesocyst found in resting cysts and may represent an incomplete packing of the fibers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is also the case in encysting Gastrostyla steinii. The lamellar structure is similar to that noted for the inner mesocyst of the gymnostome Didinium nasutum (Holt & Chapman, 1971). It appears that the "herringbone" structure of the mesocyst is a transition state for the predominantly lamellar mesocyst found in resting cysts and may represent an incomplete packing of the fibers.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, both of these protozoan species can probably be eliminated as paralytic shellfish causative agents in Southeast Alaska. Mesodinium rubrum from the Atlantic has also been described as nontoxic (Anonymous, 1968 Protozoan encystment requires considerable dedifferentiation-both physiologically (Pigon, 1959) and morphologically (Grimes, 1973;Hashimoto, 1962Hashimoto, , 1963Holt & Chapman, 1971;Kink, 1973;Tibbs, 1969 All use subject to JSTOR Terms and Conditions cytoplasmic reserves, increase in density of the cytoplasm due to intense dehydration, and a concomitant decrease in cellular volume have all been noted as characteristic of the phenomenon. Recently, a thorough study of the encystment and excystment of the hypotrich Oxytricha fallax showed that this ciliate undergoes a number of striking morphological changes (Grimes, 1973).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Some of the information obtained thus far indicates that mucocysts may be involved in the formation of the thin cystic membrane of the reproductive cyst of Tetrahymena rostrata (see Zebrun et al, 1967). Holt & Chapman (1971) reported that in Didinium other structures, which they call clathrocysts, are-in addition to mucocysts-involved in the formation of at least one of the cyst wall layers. Kawakami & Yagiu (1963a, b; 1964a-c) offer ultrastructural details concerning the cystic membranes of Colpoda.…”
Section: Cytological An1) Ultrastructural Studiesmentioning
confidence: 98%
“…Eine kleinere Anzahl ist ,,sph/irisch und yon ziemlich gleiehbleibender GrSl~e", n~mlieh 6--7 ~m. ,,Zwischen diesen beiden Formen finden sich die mannigfaltigsten Uberg/~nge, welche nieht zweifeln lassen, daI~ die einen, ns die nierenfSrmigen, eine h6here Ausbildung der anderen sind" (Miescher, 1843 (Ludvik, 1960) und bei S./usiformis (Simpson, 1966) Kattar, 1969;Grain, Golinska, 1969;Holt, Chapman, 1971 …”
Section: Besnoitia Jellisoniunclassified